Chemical Literacy of First Year Students on Carbon Chemistry - Nursida Djaen; Sri Rahayu; Yahmin Yahmin; Muntholib Muntholib (Universitas Negeri Malang, 2021)
This research aims to develop and validate chemical literacy test instruments on competency and knowledge aspects and to measure the chemical literacy of first-year science education students. Instrument development involved expert consultation, expert judgment, and testing of 114 first-year students majoring in chemistry for the analysis of item validity and instrument reliability. The instrument was developed using the Research& Development model by Borg and Gall (1989). The developed instrument consisted of 30 valid item items with Cronbach's Alpha reliability coefficient of 0.718. The analysis was carried out on 28 first-year students of the Jember State University Science Education Study Program who had studied carbon chemistry. Data analysis showed that the average score of students' chemical literacy was 59.7 in the moderate category.ReferencesAdawiyah, R., & Wisudawati, A. (2017). Pengembangan instrumen tes berbasis literasi sains. Indonesian Journal of Curriculum and Educational Technology Studies, 5(2), 112–121.Akengin, H., & Sirin, A. (2013). A comparative study upon determination of scientific literacy level of teacher candidates. Educational Research and Reviews, 8(19), 1882–1886.Arikunto, S. (2012). Dasar-dasar evaluasi pendidikan edisi 2. Jakarta: Bumi Aksara.Assessment, P. for I. S., & service), S. (Online. (2006). Assessing scientific, reading and mathematical literacy: A framework for PISA 2006. Publications de l’OCDE.Barnea, N., Dori, Y. J., & Hofstein, A. (2010). Development and implementation of inquiry-based and computerized-based laboratories: Reforming high school chemistry in Israel. Chemistry Education Research and Practice, 11(3), 218–228.Bybee, R. W. (1997). Achieving scientific literacy: From purposes to practices. ERIC.Celik, S. (2014). Chemical literacy levels of science and mathematics teacher candidates. Australian Journal of Teacher Education, 39(1), 1.Cigdemoglu, C., Arslan, H. O., & Cam, A. (2017). Argumentation to foster pre-service science teachers’ knowledge, competency, and attitude on the domains of chemical literacy of acids and bases. Chemistry Education Research and Practice, 18(2), 288–303.Cigdemoglu, Ceyhan, & Geban, O. (2015). Improving students’ chemical literacy levels on thermochemical and thermodynamics concepts through a context-based approach. Chemistry Education Research and Practice, 16(2), 302–317.De Ovira, E. (2018). PENGEMBANGAN DAN VALIDASI TES KIMIA DENGAN FRAMEWORK PISA PADA MATERI KELAS XI SEMESTER 1. Menara Ilmu, 12(80).DeBoer, G. E. (2000). Scientific literacy: Another look at its historical and contemporary meanings and its relationship to science education reform. Journal of Research in Science Teaching: The Official Journal of the National Association for Research in Science Teaching, 37(6), 582–601.Duschl, R. A., & Osborne, J. (2002). Supporting and promoting argumentation discourse in science education.Gall, M. D., & Borg, W. R. (1989). Educational Research. A Guide for Preparing a Thesis or Dissertation Proposal in Education. ERIC.Gerlach, K., Trate, J., Blecking, A., Geissinger, P., & Murphy, K. (2014). Valid and reliable assessments to measure scale literacy of students in introductory college chemistry courses. Journal of Chemical Education, 91(10), 1538–1545.Gurel, D. K., Eryilmaz, A., & McDermott, L. C. (2015). A review and comparison of diagnostic instruments to identify students’ misconceptions in science. Eurasia Journal of Mathematics, Science and Technology Education, 11(5), 989–1008.Impey, C. (2013). Science literacy of undergraduates in the united states. Organizations, people and strategies in astronomy, 2(2), 353–364.Kemendikbud, R. I. (2014). Permendikbud No. 49 Tahun 2014 tentang Standar Nasional Pendidikan Tinggi. Jakarta: Kemendikbud.Laugksch, R. C., & Spargo, P. E. (1996). Development of a pool of scientific literacy test-items based on selected AAAS literacy goals. Science Education, 80(2), 121–143.Miller, J. D. (1983). Scientific literacy: A conceptual and empirical review. Daedalus, 29–48.Muntholib, M., Ibnu, S., Rahayu, S., Fajaroh, F., Kusairi, S., & Kuswandi, B. (2020). Chemical Literacy: Performance of First Year Chemistry Students on Chemical Kinetics. Indonesian Journal of Chemistry.Norris, S. P., & Phillips, L. M. (2003). How literacy in its fundamental sense is central to scientific literacy. Science education, 87(2), 224–240.Norris, S. P., & Phillips, L. M. (2009). Scientific literacy. The Cambridge handbook of literacy, 271–285.OECD, F. (2016). FDI in Figures. Organisation for European Economic Cooperation Paris.OECD, P. (2015). Assessment and analytical framework: Science. Reading, Mathematic and Financial Literacy,(Interscience: Paris, 2016), 24–25.Osborne, J., & Dillon, J. (2008). Science education in Europe: Critical reflections (Vol. 13). London: The Nuffield Foundation.Permendikbud, R. I. (t.t.). Nomor 59 tahun 2014 Tentang Kurikulum 2013 Sekolah Menengah Atas. Madrasah Aliyah, Jakarta: Depdikbud.Rahayu, S. (2017). Mengoptimalkan aspek literasi dalam pembelajaran kimia abad 21. Prosiding Seminar Nasional Kimia UNY, 319–324.Rifal, M., & Rauf, W. (2018). Analisis Penggunaan Bahan Bakar Etanol-Pertalite Pada Motor Honda Scoopy 110 cc. Gorontalo Journal of Infrastructure and Science Engineering, 1(1), 55–64.Shwartz, Y., Ben-Zvi, R., & Hofstein, A. (2006). The use of scientific literacy taxonomy for assessing the development of chemical literacy among high-school students. Chemistry Education Research and Practice, 7(4), 203–225.Sumarni, W., Supardi, K. I., & Widiarti, N. (2018). Development of assessment instruments to measure critical thinking skills. IOP Conference Series: Materials Science and Engineering, 349(1), 012066.Sunarti, T. (2015). Pemahaman literasi sains mahasiswa calon guru fisika Universitas Negeri Surabaya. Seminar Nasional Fisika dan Pembelajarannya, 2015, 34–39.Tarhan, L., & Sesen, B. A. (2010). Investigation the effectiveness of laboratory works related to “acids and bases” on learning achievements and attitudes toward laboratory. Procedia-Social and Behavioral Sciences, 2(2), 2631–2636.Thummathong, R., & Thathong, K. (2018). Chemical literacy levels of engineering students in Northeastern Thailand. Kasetsart Journal of Social Sciences, 39(3), 478–487.Traiwichitkhun, D., & Wongwanich, S. (2014). Causal Model of Research Competency via Scientific Literacy of Teacher and Student Lertporn Udompong. Procedia-Social and Behavioral Sciences, 116, 1581–1586.Turiman, P., Omar, J., Daud, A. M., & Osman, K. (2012). Fostering the 21st century skills through scientific literacy and science process skills. Procedia-Social and Behavioral Sciences, 59, 110–116.